Insulation composition for battery device, method for preparing the same, sheet formed using the same, and battery module comprising the same

By using different fiber support and process steps in the composite material to manufacture battery insulation materials, the problems of insufficient thermal insulation, fire resistance and mechanical properties in the prior art are solved, and efficient insulation and fire resistance are achieved, while reducing dust generation and cost.

JP2025018937AActive Publication Date: 2025-02-06SAMSUNG SDI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024092201
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-06-06
Publication Date
2025-02-06
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The prior art is difficult to provide battery insulation materials with efficient thermal insulation, fire resistance and mechanical properties, and there are problems of dust generation.

Method used

Using composite materials including the first and second fiber support, aerogel, binder, dispersant or a combination thereof, battery insulating materials are manufactured through different fiber support and process steps, including the use of different fiber support such as glass fiber and silica asbestos, controlling material proportions and particle sizes, using aqueous polymer binders and dispersants, controlling solvent ratios, mixing and coating processes.

Benefits of technology

It realizes efficient thermal insulation, fire resistance and mechanical properties of battery insulating materials, while reducing dust generation and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018937000001_ABST
    Figure 2025018937000001_ABST
Patent Text Reader

Abstract

To provide an aerogel composition having improved thermal insulation, fire resistance, mechanical properties, and / or dustiness, a method for preparing the aerogel composition, a battery insulation sheet formed using the aerogel composition, and a method for preparing the battery insulation sheet.SOLUTION: The present invention relates to an aerogel composition for battery insulation sheets, the aerogel composition including a reinforcement material including a first fibrous support and a second fibrous support, an aerogel, a functional material including a binder, a dispersant, or a combination thereof, and a solvent, wherein the first fibrous support and the second fibrous support have different ingredients. The present invention also relates to a method for preparing the aerogel composition, a battery insulation sheet formed using the aerogel composition, and a method for preparing the battery insulation sheet.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aerogel composition for a battery insulation sheet, a method for producing the same, a battery insulation sheet formed using the same, and a method for producing the same. [Background technology]

[0002] Secondary batteries are power storage systems that provide excellent energy density by converting electrical energy into chemical energy and storing it. Unlike primary batteries, which cannot be recharged, secondary batteries can be recharged, and are widely used in IT devices such as smartphones, cellular phones, laptops, and tablet PCs. In recent years, interest in electric vehicles has increased to prevent environmental pollution, and high-capacity secondary batteries are being adopted for electric vehicles. Such secondary batteries are required to have characteristics such as high density, high output, and stability.

[0003] On the other hand, when a battery contains a large number of high-capacity cells such as lithium secondary batteries, one cell may overheat for some reason and experience thermal runaway, adversely affecting other adjacent cells, so it is required that adjacent cells are thermally insulated from each other.

[0004] Therefore, conventionally, a plate material or an insulating resin plate is placed between the cells to insulate and heat the adjacent cells.

[0005] The above information disclosed in the Background of the Invention is intended to enhance the understanding of the background of the present invention only, and may therefore include information that does not constitute prior art. Summary of the Invention [Problem to be solved by the invention]

[0006] One embodiment provides an aerogel composition having excellent heat insulation, fire resistance, mechanical properties, and low dust properties, a manufacturing method thereof, a battery insulation sheet formed using the aerogel composition, and a manufacturing method thereof. [Means for solving the problem]

[0007] One embodiment provides an aerogel composition for a battery insulation sheet, comprising a reinforcing material including a first fibrous support and a second fibrous support, an aerogel, a functional substance including a binder, a dispersant, or a combination thereof, and a solvent, wherein the first fibrous support and the second fibrous support have different components.

[0008] The material of each of the first fibrous support and the second fibrous support may be one or more selected from the group consisting of glass, silica, basalt, alumina, silicon carbide, boron, ceramic, and quartz, and the form of each of the first fibrous support and the second fibrous support may be one or more selected from the group consisting of powder, fiber, wool, chop, felt, batting, and lofty batting.

[0009] The first fibrous support may be silica fiber, and the second fibrous support may be glass wool or silica wool.

[0010] The first fibrous support and the second fibrous support may be included in a weight ratio of 1:5 to 5:1.

[0011] Each of the first and second fibrous supports may have an average length of 50 μm to 20,000 μm and an average diameter of 0.1 μm to 30 μm.

[0012] The aerogel has a BET specific surface area of ​​500 m 2 / g~1,000m 2 / g.

[0013] The average particle size of the aerogel (D 50 ) may be 5 μm to 200 μm.

[0014] The binder includes an aqueous polymer binder, and the aqueous polymer binder may be at least one selected from the group consisting of aqueous polymers, anionic water-soluble polymers, cationic water-soluble polymers, and water-dispersible polymers.

[0015] The binder may be contained in an amount of 0.5% by weight to 20% by weight based on the total solid content of the aerogel composition.

[0016] The dispersant may be one or more selected from the group consisting of surfactants and phosphate salts.

[0017] The dispersant may be included in an amount of 0.1% by weight to 6% by weight based on the total solid content of the aerogel composition.

[0018] The solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.

[0019] The weight ratio of the solvent to the total solid content of the aerogel composition may be 1:1 to 1:90.

[0020] The aerogel composition may contain 5% by weight to 70% by weight of the reinforcing material, 10% by weight to 90% by weight of the aerogel, and 0.5% by weight to 20% by weight of the functional material, based on the total solid content of the aerogel composition.

[0021] Another embodiment provides a method for producing an aerogel composition for a battery insulation sheet, the method including: mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to produce an aerogel mixture; and mixing the aerogel mixture with a reinforcing material to produce an aerogel composition, the reinforcing material including a first fibrous support and a second fibrous support, the first fibrous support and the second fibrous support having different components.

[0022] Yet another embodiment provides a battery insulation sheet including a first substrate, a second substrate, and an aerogel layer formed between the first substrate and the second substrate, the aerogel layer being formed using the aerogel composition.

[0023] Each of the first substrate and the second substrate may include a resin, a metal, an inorganic material other than a metal, or any composite thereof.

[0024] Within the aerogel layer, each of the first and second fibrous supports may have a vertical orientation, a horizontal orientation, or a combination thereof.

[0025] Yet another embodiment provides a method for producing a battery insulation sheet, the method including: applying the aerogel composition onto a first substrate; and laminating a second substrate onto the applied aerogel composition to produce a laminate.

[0026] The method may further comprise the step of pressing and drying the laminate after the step of producing the laminate. Effect of the Invention

[0027] The battery insulation sheet manufactured using the aerogel composition according to an embodiment has excellent thermal insulation properties and fire resistance, as well as excellent mechanical properties such as durability and compressive properties, and can be manufactured at low cost and prevent the generation of aerogel dust during the manufacturing process or use. [Brief description of the drawings]

[0028] [Figure 1] 1 is a schematic diagram showing a structure of a battery insulation sheet according to an embodiment; [Diagram 2] FIG. 2 is a schematic diagram showing a battery insulation sheet according to an embodiment formed between a plurality of cells. [Diagram 3] 2 is a SEM image of an aerogel layer of the battery insulation sheet according to Example 1. [Figure 4]1 is a SEM image of an aerogel layer of a battery insulation sheet according to Example 4. [Diagram 5] 13 is a SEM image of an aerogel layer of the battery insulation sheet according to Example 7. [Figure 6] 1 is a SEM image of an aerogel layer of a battery insulation sheet according to Comparative Example 1. [Figure 7] 4 is a photograph showing the results of fire resistance evaluation of the battery insulation sheets of Examples 1 and 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Although the present invention will be described in detail below so as to be easily understood by those skilled in the art, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.

[0030] Insulation materials are materials that prevent the movement of heat from high temperature areas to low temperature areas, and are used in a variety of industrial fields, including refrigerators, freezer warehouses, and buildings, as well as the aircraft, electronic parts, and automotive industries.

[0031] Such a heat insulating material should have excellent heat insulating performance due to low thermal conductivity, and is also required to have sufficient mechanical strength to maintain such heat insulating performance.

[0032] Meanwhile, aerogel is a transparent or translucent cutting-edge material with a nanoporous structure, and has very low density and low thermal conductivity. As such, it not only has great potential as an insulating material, but is also considered a highly efficient super-insulating material that can be used in a variety of industrial fields.

[0033] Furthermore, the greatest advantage of aerogel is that it exhibits lower thermal conductivity than conventional organic insulation materials such as styrofoam, and that it solves the fatal weaknesses of organic insulation materials, namely, vulnerability to fire and the generation of harmful gases during a fire.

[0034] However, in general, aerogel has a very low strength due to its high brittleness, i.e., it is easily broken even by a small impact, and it is difficult to process it into a very thin thickness and shape. Therefore, despite its excellent thermal insulation properties, it is very difficult to manufacture a thermal insulation material by using aerogel alone. The aerogel composition according to one embodiment includes a reinforcing material including a first fibrous support and a second fibrous support, an aerogel, a functional material including a binder, a dispersant, or a combination thereof, and a solvent, and the first fibrous support and the second fibrous support may have different components. The fact that the components of the first fibrous support and the second fibrous support are different from each other may mean that at least one of the material and the shape of each fibrous support is different.

[0035] The battery insulation sheet manufactured from the aerogel composition comprising the above components has excellent insulation properties, fire resistance and mechanical properties, has low manufacturing costs, and can prevent the generation of aerogel dust during the manufacturing process and use, thereby improving the safety of the battery.

[0036] In one embodiment, the reinforcing material includes a first fibrous support and a second fibrous support having different components, and the mechanical properties of the battery insulation sheet formed using the same can be improved.

[0037] Each of the first fibrous support and the second fibrous support may include fibers used as supports for ordinary thermal insulation materials. Hereinafter, even if the term "first" or "second" is not specified, the fibrous support can refer to each of the first fibrous support and the second fibrous support.

[0038] The fibrous support may be one or more fibers selected from the group consisting of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymeric fibers.

[0039] The natural fibers may be, for example, one or more selected from the group consisting of hemp, jute, flax, coir, hemp, and cellulose.

[0040] The ceramic fibers may be one or more selected from the group consisting of silicon carbide, silicon nitride, boron nitride, and aluminum silicon carbide.

[0041] The mineral fibers may be, for example, mineral fibers comprising one or more selected from the group consisting of basalt, wollastonite, alumina, boron, quartz, silica, and slag.

[0042] The polymer fiber may be, for example, one or more selected from the group consisting of nylon, polyimide, polyamide, polybenzimidazole, polybenzoxazole, polyamideimide, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyethylene (PE), and polypropylene (PP). As a specific example, the polymer fiber may include, but is not limited to, one or more of polyimide, polyamide, and polybenzimidazole.

[0043] The form of the fibrous support may be, for example, one or more of powder, fiber, wool, chop, felt, batting, and lofty batting, but is not limited thereto. Fiber may refer to a general shape of a long, thin thread.

[0044] The material of each of the first fibrous support and the second fibrous support may be one or more selected from the group consisting of glass, silica, basalt, alumina, silicon carbide, boron, ceramic, and quartz, and the form of each of the first fibrous support and the second fibrous support may be one or more selected from the group consisting of powder, fiber, wool, chop, felt, batting, and lofty batting. As a specific example, the first fibrous support may be silica fiber or glass chopped strand, and the second fibrous support may be glass wool or silica wool. As a more specific example, the first fibrous support may be silica fiber, and the second fibrous support may be glass wool or silica wool. In this way, by including the first fibrous support and the second fibrous support that are different from each other, the mechanical properties of the battery insulation sheet can be further improved.

[0045] The first fibrous support and the second fibrous support may be included in a weight ratio of 1:5 to 5:1, 1:4 to 4:1, or 1:3 to 3:1. By including the first fibrous support and the second fibrous support in a weight ratio within this range, the mechanical properties of the battery insulation sheet can be further improved.

[0046] The average length of the fibrous support may be, for example, 50 μm to 20,000 μm, 100 μm to 12,000 μm, 100 μm to 5,000 μm, or 3,000 μm to 12,000 μm. Here, the average length of the fibrous support may mean the average length of each of the first fibrous support and the second fibrous support. When the fibrous support has an average length within this range, the aerogel layer can be formed firmly and the mechanical properties can be improved.

[0047] The average diameter of the fibrous support may be, for example, 0.1 μm to 30 μm, 8 μm to 20 μm, 8 μm to 12 μm, or 10 μm to 20 μm. Here, the average diameter of the fibrous support can mean the average diameter of each of the first fibrous support and the second fibrous support. By including a fibrous support having an average diameter within this range, the structure of the aerogel layer can be made firm, and the production cost can be reduced.

[0048] The first fibrous support may have an average diameter of 8 μm to 12 μm and an average length of 100 μm to 20,000 μm, and the second fibrous support may have an average diameter of 10 μm to 20 μm and an average length of 3 μm to 12 μm. By including a first fibrous support and a second fibrous support having average diameters and average lengths within the ranges, the porosity and orientation can be improved, and the compression characteristics can be improved.

[0049] The content of the reinforcing material may be 5% by weight to 70% by weight, 25% by weight to 60% by weight, or 30% by weight to 50% by weight based on the total solid content of the aerogel composition. When a battery insulation sheet is produced using an aerogel composition containing a fibrous support within this range, the mechanical properties of the battery insulation sheet can be improved.

[0050] In one embodiment, the aerogel has a BET specific surface area of ​​500 m 2 / g~1,000m 2 For example, the aerogel may have a BET specific surface area of ​​500 m 2 / g~950m 2 / g, 550m 2 / g~950m 2 / g, or 600m 2 / g~900m 2 By including an aerogel having a BET specific surface area value within this range, it is possible to provide a heat insulating sheet that can effectively prevent heat transfer and heat propagation between a plurality of cells.

[0051] Average particle size of aerogel (D 50) may be 5 μm to 200 μm, 10 μm to 100 μm, or 20 μm to 50 μm. By including an aerogel having an average particle size within this range, it is possible to improve the insulating properties and retard heat transfer between multiple cells.

[0052] Average particle size (D 50 ) can be measured, for example, using the laser diffraction method or scanning electron microscope (SEM) photographs, and the average particle size (D 50 ) can be defined as the particle size at 50% of the particle size distribution (the particle size corresponding to 50% of the cumulative volume of the particle size distribution).

[0053] The content of the aerogel may be 10% by weight to 90% by weight, 30% by weight to 70% by weight, or 40% by weight to 60% by weight based on the total solid content of the aerogel composition. When a battery insulation sheet is produced using an aerogel composition containing an aerogel within this range, the heat insulating property of the battery insulation sheet can be improved.

[0054] In one embodiment, the binder may include a water-based polymer binder. For example, the water-based polymer binder may be one or more selected from the group consisting of a water-based polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and a water-dispersible polymer.

[0055] The water-based polymer may be, for example, one or more selected from the group consisting of polyvinyl alcohol, polyethylene oxide, polyacrylamide, and polyvinylpyrrolidone, but is not limited thereto.

[0056] The anionic water-soluble polymer may include at least one selected from the group consisting of polymers having functional groups of carboxylic acid, sulfonic acid, sulfate, phosphate, and salts thereof. For example, the anionic water-soluble polymer may be a polymer having a carboxylic acid group, and a specific example thereof may include, but is not limited to, polymaleic acid.

[0057] The cationic water-soluble polymer may include at least one selected from the group consisting of polymers having functional groups of amine, ammonium, phosphonium, sulfonium, and salts thereof. For example, the cationic water-soluble polymer may be a polymer having an amine group, and a specific example may be at least one selected from the group consisting of polyethylene amine and polyamine, but is not limited thereto.

[0058] The water-dispersible polymer may be at least one selected from the group consisting of water-dispersible polyurethane and water-dispersible polyester, but is not limited thereto.

[0059] The binder may include a water-based polymer and a water-dispersible polymer, for example, a water-based polymer having binder properties as well as dispersion properties, and a water-dispersible polyurethane having fire-resistant properties, and a specific example may include polyvinyl alcohol and a water-dispersible polyurethane.

[0060] The weight ratio of the aqueous polymer and the water-dispersible polymer may be 1:1 to 1:5, 1:1 to 1:4, or 1:2 to 1:3. By using the aqueous polymer and the water-dispersible polymer in combination within this weight ratio range, the heat insulation properties, dust resistance, and compression properties of the heat insulating sheet can be further improved as well as the fire resistance and mechanical properties.

[0061] The content of the binder may be 0.5% by weight to 20% by weight, 2% by weight to 15% by weight, or 8% by weight to 15% by weight based on the total solid content of the aerogel composition. When the aerogel composition containing the binder within this range is used to produce the battery insulation sheet, the dust characteristics of the battery insulation sheet can be improved.

[0062] In one embodiment, the dispersant may be one or more selected from the group consisting of surfactants and phosphate-based salts.Specific examples of the dispersant include, but are not limited to, any one or more of nonionic surfactants, anionic surfactants, amphoteric surfactants, natural surfactants such as lecithin, and phosphates.

[0063] When a dispersant is further contained, the dispersion of the aerogel in the composition is improved, and the fibrous support and the aerogel can be uniformly dispersed.

[0064] The content of the dispersant may be 0.1% to 6% by weight, 0.1% to 5% by weight, or 0.1% to 3% by weight based on the total solid content of the aerogel composition. When the dispersant is contained within this range, the aerogel composition can be produced at low cost, and thus a battery insulation sheet having excellent heat insulation properties, fire resistance, mechanical properties, and dust properties can be produced.

[0065] In one embodiment, the binder and the dispersant may be included in a weight ratio of 1:0.001 to 1:0.67, 1:0.001 to 1:0.5, or 1:0.001 to 1:0.3. When the binder and the dispersant are used in combination in a weight ratio within this range, the aerogel may be more uniformly dispersed in the aerogel layer.

[0066] In one embodiment, the reinforcing material may comprise 25% by weight to 60% by weight, the aerogel may comprise 30% by weight to 70% by weight, and the binder may comprise 2% by weight to 15% by weight, based on the total solid content of the aerogel composition.

[0067] As a specific example, the aerogel composition may contain 30% to 50% by weight of the reinforcing material, 40% to 60% by weight of the aerogel, and 8% to 15% by weight of the binder, based on the total solid content of the aerogel composition. By forming the aerogel composition within these ranges, it is possible to realize excellent heat insulation and fire resistance, while at the same time improving mechanical properties, and to prevent dust generation by improving the bonding strength between the reinforcing material and the aerogel.

[0068] In one embodiment, the aerogel composition may contain 25% by weight to 60% by weight of the reinforcing material, 30% by weight to 70% by weight of the aerogel, 2% by weight to 15% by weight of the binder, and 0.1% by weight to 5% by weight of the dispersant, based on the total solid content of the aerogel composition.

[0069] As a specific example, the aerogel composition may contain 30% to 50% by weight of the reinforcing material, 40% to 60% by weight of the aerogel, 5% to 10% by weight of the binder, and 0.1% to 3% by weight of the dispersant, based on the total solid content of the aerogel composition. By forming the aerogel composition within these ranges, the dispersibility of the aerogel can be improved, excellent thermal insulation and fire resistance can be achieved, and at the same time, mechanical properties can be further improved, and the cohesive force between the reinforcing material and the aerogel can be improved to prevent dust generation.

[0070] In one embodiment, the solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.

[0071] The polar solvent may be water, an alcohol-based solvent, or a combination thereof.

[0072] The water may include, for example, purified water, ultra-pure water, or a combination thereof.

[0073] The alcohol-based solvent may be, for example, one or more selected from the group consisting of methanol, ethanol, propanol, pentanol, butanol, hexanol, ethylene glycol, propylene glycol, diethylene glycol, and glycerol, but is not limited thereto.

[0074] The non-polar solvent may include a hydrocarbon-based solvent, for example, one or more selected from the group consisting of hexane, pentane, heptane, toluene, and benzene, and more preferably, an alkane solvent such as hexane, or a mixture containing an alkane solvent, but is not limited thereto.

[0075] The solvent may include water. When water is used as a solvent, raw material costs and post-processing costs can be effectively reduced. However, when water is used as a solvent, there is a problem that it is not easy to mix with the hydrophobic aerogel. In one embodiment, the aerogel is uniformly dispersed by controlling the mixing process design, mixing conditions, addition and amount of binder and dispersant, etc. When the aerogel is uniformly dispersed in the composition in this way, a battery insulation sheet having excellent insulation properties, fire resistance, mechanical properties, and low dust properties can be formed with a thin thickness without using a large amount of binder.

[0076] The solvent may be contained in such a way that the weight ratio of the solvent to the total amount of solids in the aerogel composition is 1:1 to 1:90. For example, the weight ratio of the solvent to the total amount of solids in the aerogel composition may be 1:50 to 1:70, 1:20 to 1:30, or 1:2 to 1:10. By controlling the weight ratio of the solvent to the total amount of solids within the range, the viscosity can be controlled and the aerogel layer can be coated.

[0077] In one embodiment, the aerogel composition may further include a silane-based compound. The silane-based compound may be, for example, one or more selected from the group consisting of 3-(trimethoxysilyl)propylmethacrylate, methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, octadecyltrimethoxysilane, ethyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane. When the silane-based compound is further included, the dispersibility may be further improved.

[0078] In one embodiment, the composition may further optionally include additives such as wetting agents, emulsifiers, compatibilizers, viscosity adjusters, pH adjusters, stabilizers, antioxidants, acidic or basic scavengers, metal deactivators, antifoaming agents, antistatic agents, thickeners, adhesion improvers, binders, flame retardants, impact modifiers, pigments, dyes, colorants, and deodorizers.

[0079] According to one embodiment, a method for producing an aerogel composition includes the steps of: mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to produce an aerogel mixture; and mixing the aerogel mixture with a reinforcing material to produce an aerogel composition, the reinforcing material including a first fibrous support and a second fibrous support, the first fibrous support and the second fibrous support having different components.

[0080] In the process of preparing a solvent mixture by mixing a functional material in a solvent, a binder may be mixed in the solvent, or a binder and a dispersant may be mixed in the solvent. Here, the specific description of the solvent, binder, and dispersant may be as described above.

[0081] In the process of preparing the aerogel mixture by mixing the solvent mixture with the aerogel, the aerogel may be added in a powder form, and the specific description of the aerogel may be as described above.

[0082] In the step of producing an aerogel composition by mixing an aerogel mixture with a reinforcing material, the specific explanations regarding the first fibrous support, the second fibrous support, and the reinforcing material may be as described above.

[0083] In each of the steps of preparing a solvent mixture by mixing a functional material including a binder, a dispersant, or a combination thereof with a solvent, preparing an aerogel mixture by mixing the solvent mixture with an aerogel, and preparing an aerogel composition by mixing the aerogel mixture with a reinforcing material, a mixer may be used during mixing. For example, the mixer may include, but is not limited to, a planetary mixer and a thinky mixer.

[0084] As a specific example, a planetary mixer can be used to mix the solvent mixture and the aerogel. When the solvent mixture and the aerogel are mixed using a planetary mixer, the aerogel can be uniformly dispersed in the solvent.

[0085] A planetary mixer may be a piece of equipment that can be used to mix or stir different materials together to produce a homogenous mixture. It may include blades that are capable of planetary motion.

[0086] In one embodiment, the planetary mixer may include any one or more of one or more planetary blades and one or more high-speed dispersion blades. As a specific example, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades.

[0087] The planetary blades and high speed dispersion blades rotate continuously about their axes, and the rotational speed may be expressed in units of rotations per minute (rpm).

[0088] In one embodiment, the planetary mixer may include a first blade and a second blade having different rotation axes. For example, the first blade may be a low-speed blade, and the second blade may be a high-speed blade. Here, low speed and high speed refer to the relative rotation speeds of the first blade and the second blade. As a specific example, the first blade may be an open blade, and the second blade may be a Despa blade.

[0089] The rotation speed of the first blade may be, for example, 10 rpm to 100 rpm, 10 rpm to 60, or 30 rpm to 70 rpm, and the rotation speed of the second blade may be, for example, 100 rpm to 2000 rpm, 100 rpm to 1000 rpm, 300 rpm to 1700 rpm, or 500 rpm to 1700 rpm.

[0090] When the functional material is mixed in the solvent, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 600 rpm to 1000 rpm, or 700 rpm to 800 rpm. By mixing the solvent and the functional material in this manner, a solvent mixture in which the binder, dispersant, or a combination thereof is uniformly dispersed is produced, and aerogel mixing can be more easily performed in the subsequent process.

[0091] When mixing the solvent mixture and the aerogel, the rotation speed of the first blade of the mixer may be 30 rpm to 70 rpm, 40 rpm to 70 rpm, or 60 rpm to 70 rpm, and the rotation speed of the second blade may be 500 rpm to 1700 rpm, 600 rpm to 1600 rpm, or 800 rpm to 1500 rpm. By adding the aerogel to the solvent mixture and mixing it in this way, it is possible to prevent the aerogel from agglomerating with each other and induce uniform dispersion.

[0092] When mixing the aerogel mixture and the fibrous support, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 400 rpm to 1500 rpm, or 800 rpm to 1200 rpm. When the aerogel mixture and the fibrous support are mixed in this way, the air bubbles in the composition are removed, the viscosity is adjusted, and the fibrous support is easily dispersed between the uniformly dispersed aerogel, so that the aerogel may be present in the composition in a form in which the periphery of the fibrous support is covered by the aerogel. Here, a binder is present between the aerogel and the fibrous support, which can improve the binding force between the aerogel and the fibrous support.

[0093] In one embodiment, the battery insulation sheet includes a first substrate, a second substrate, and an aerogel layer formed between the first substrate and the second substrate, and the aerogel layer may be formed using the aerogel composition according to one embodiment described above.

[0094] FIG. 1 is a schematic diagram showing the structure of a battery insulation sheet according to one embodiment.

[0095] Referring to FIG. 1, in one embodiment, the battery insulation sheet 100 may have a structure including a first substrate 110, an aerogel layer 120 formed on the first substrate 110, and a second substrate 130 formed on the aerogel layer 120. In addition, in the aerogel layer 120, the first fibrous support 121 is shown by a thick line, and the second fibrous support 122 is shown by a thin line, and other components are omitted in order to specifically show the dispersion form of the first fibrous support 121 and the second fibrous support 122, and therefore it should not be interpreted that the aerogel layer does not contain components other than the reinforcing material. In the aerogel layer 120, the first fibrous support 121 and the second fibrous support 122 may be vertically and horizontally oriented, respectively. In addition, in FIG. 1, the first substrate 110 and the second substrate 130 may be formed of the same or different materials.

[0096] By forming an aerogel layer using the aerogel composition according to one embodiment between the first substrate and the second substrate, the battery insulation sheet has improved mechanical properties in addition to thermal insulation and fire resistance, and can prevent the aerogel from falling off and generating dust when the battery insulation sheet is manufactured or installed inside an apparatus.

[0097] FIG. 2 is a schematic diagram showing a battery insulation sheet according to one embodiment formed between a plurality of cells.

[0098] Referring to FIG. 2, the battery insulation sheet 100 according to an embodiment may be formed between each of the cells 200 in a battery module including the plurality of cells 200. Here, the upper and lower surfaces of the battery insulation sheet, i.e., the first and second substrates of the battery insulation sheet, may be disposed to face the adjacent cells, respectively. By forming the battery insulation sheet 100 according to an embodiment between each of the plurality of cells 200, it is possible to provide a battery module and a battery pack including the same, which are safer, by blocking a flame in advance inside the cell and minimizing the spread of the flame to other cells.

[0099] In the battery insulation sheet, the specific description of the aerogel composition forming the aerogel layer may be as described above.

[0100] The first and second substrates may be made of various materials such as resin, metal, inorganic material other than metal, or composites thereof, and are not limited to their types. The form of the substrate may be a film, thin film, sheet, or the like, and is not particularly limited.

[0101] The resin may be, for example, one or more selected from the group consisting of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and polyamide.

[0102] The metal may be, for example, one or more selected from the group consisting of copper, nickel, cobalt, iron, chromium, vanadium, palladium, ruthenium, rhodium, molybdenum, tungsten, iridium, silver, gold, and platinum. When using a metal substrate, the substrate may be subjected to anticorrosive treatment, insulating treatment, etc., as necessary.

[0103] The inorganic material may be one or more selected from the group consisting of calcium carbonate (CaCO3), talc, and mica.

[0104] As a specific example, the first substrate and the second substrate may include an inorganic material, and more specifically, may include mica, in which case the heat insulating property and durability of the heat insulating sheet can be improved.

[0105] In one embodiment, the first fibrous support and the second fibrous support may each have a vertical orientation, a horizontal orientation, or a combination thereof in the aerogel layer. As a specific example, the first fibrous support and the second fibrous support may each have a uniform vertical orientation and a uniform horizontal orientation in the aerogel layer. In this case, the compression characteristics of the aerogel layer are further improved, and the pressure on the adjacent cells during the cell deterioration and expansion process can be absorbed, thereby improving the safety of the battery.

[0106] In one embodiment, the aerogel layer may be formed in a single layer structure or a multi-layer structure. When the aerogel layer is formed in a multi-layer structure, the aerogel layer may be formed in 2 to 10 layers, 2 to 7 layers, or 2 to 5 layers.

[0107] A method for manufacturing a battery insulation sheet according to an embodiment may include a step of applying an aerogel composition according to an embodiment onto a first substrate, and a step of laminating a second substrate onto the applied aerogel composition to manufacture a laminate.

[0108] In the method for producing a battery insulation sheet, the specific description regarding the substrate and the aerogel composition may be as described above.

[0109] The step of applying the aerogel slurry onto the first substrate and the step of laminating the second substrate onto the applied aerogel slurry may be carried out by a conventional method.

[0110] The step of applying the aerogel slurry onto the first substrate may be performed once, or repeated two or more times.

[0111] In one embodiment, after producing the laminate, the method may further include pressing and drying the laminate.

[0112] The drying step may be carried out, for example, at a temperature of 25° C. to 100° C., 45° C. to 90° C., or 60° C. to 85° C. When drying is performed at such a temperature, a robust aerogel layer is formed on the substrate without a separate adhesive member or bonding agent while preventing detachment between the substrate and the aerogel layer, and a coating layer can be formed in such a way that the periphery of the plurality of dispersed first fibrous supports and second fibrous supports is coated with aerogel.

[0113] According to an embodiment, a battery insulation sheet can be manufactured by a simple method of applying an aerogel composition onto a first substrate, laminating a second substrate on the aerogel composition to manufacture a laminate, and then pressing and drying the laminate. This method does not require the use of a separate adhesive or the formation of an adhesive layer, and because the aerogel is uniformly dispersed, the battery insulation sheet can have excellent insulation properties, fire resistance, mechanical properties, and low dust properties even at a thin thickness.

[0114] Specific examples of the present invention will be presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereto. Furthermore, since the contents not described here can be sufficiently inferred by a person skilled in the art, the description thereof will be omitted.

[0115] (Battery insulation sheet manufacturing) Example 1 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) was added as a binder to ultrapure water as a solvent, and then mixed under conditions of an open blade of 30 rpm and a despa blade of 700 rpm to produce a solvent mixture. 2 Aerogel having a particle size of 1 / g was added and mixed under the conditions of open blade 70 rpm and Despa blade 1500 rpm to produce an aerogel mixture. Silica fiber (first fibrous support) and glass wool (second fibrous support) were added as reinforcing materials in a weight ratio of 1:3 to the aerogel mixture, and then mixed under the conditions of open blade 30 rpm and Despa blade 1200 rpm to produce an aerogel composition. Here, a planetary mixer (DIENTEK, PT-005) was used for mixing.

[0116] The solids content of the produced aerogel composition was determined to be 50 wt. % aerogel, 40 wt. % reinforcing material, and 10 wt. % polyvinyl alcohol.

[0117] 2. Battery insulation sheet manufacturing The aerogel composition was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was sandwich-type laminated and coated by rolling. The aerogel layer was then formed by drying at 60°C for 24 hours to produce a battery insulation sheet. The total thickness of the battery insulation sheet was confirmed to be 1.38 mm.

[0118] Example 2 The same method as in Example 1 was used to prepare an aerogel composition, except that silica fiber and glass wool were added to the aerogel mixture in a weight ratio of 1:1 and mixed to prepare an aerogel composition.

[0119] Example 3 The same method as in Example 1 was used to produce an aerogel composition, except that silica fiber and glass wool were added to the aerogel mixture in a weight ratio of 3:1 and mixed to produce the aerogel composition.

[0120] Example 4 The same method as in Example 1 was used to produce an aerogel composition, except that silica fiber and glass wool were added to the aerogel mixture in a weight ratio of 1:4 and mixed to produce the aerogel composition.

[0121] Example 5 The same method as in Example 1 was used to prepare an aerogel composition, except that silica fiber and glass wool were added to the aerogel mixture in a weight ratio of 4:1 and mixed to prepare an aerogel composition.

[0122] Example 6 The aerogel composition was produced in the same manner as in Example 1, except that ceramic wool was added to the aerogel mixture instead of glass wool and mixed to produce the aerogel composition.

[0123] Example 7 The aerogel composition was produced in the same manner as in Example 1, except that glass chopped strands were added to the aerogel mixture instead of silica fibers and mixed to produce the aerogel composition.

[0124] Example 8 The same method as in Example 1 was used to produce an aerogel composition, except that glass chopped strands were added to the aerogel mixture instead of silica fiber, and ceramic wool was added to the aerogel mixture instead of glass wool, and the mixture was mixed to produce an aerogel composition.

[0125] Example 9 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) as a binder and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant were added to the ultrapure water solvent, and then mixed with an open blade at 30 rpm and a despa blade at 700 rpm to produce a solvent mixture. 2 After adding aerogel having a mass of 1000g / g, the mixture was mixed under the conditions of open blade 70 rpm and Despa blade 1500 rpm to produce an aerogel mixture. After adding silica fiber and glass wool as reinforcing materials in a weight ratio of 1:3 to the aerogel mixture, the mixture was mixed under the conditions of open blade 30 rpm and Despa blade 1200 rpm to produce an aerogel composition. Here, a planetary mixer (DN Tech, PT-005) was used for mixing.

[0126] The solids content of the produced aerogel composition was determined to be 50 wt. % aerogel, 40 wt. % reinforcing material, 9.9 wt. % polyvinyl alcohol, and 0.1 wt. % dispersant.

[0127] 2. Battery insulation sheet manufacturing The aerogel composition was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was sandwich-type laminated and coated by rolling. The aerogel layer was then formed by drying at 60°C for 24 hours to produce a battery insulation sheet. The total thickness of the battery insulation sheet was confirmed to be 1.38 mm.

[0128] Comparative Example 1 1. Aerogel Composition Preparation The solvent was ultrapure water, the binder was polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)), and the BET value was 800m 2 / g of aerogel was added and mixed to prepare an aerogel composition. Here, a planetary mixer (DN Tech, PT-005) was used for mixing.

[0129] The solids content of the produced aerogel composition was determined to be 50 wt. % aerogel and 50 wt. % polyvinyl alcohol.

[0130] 2. Battery insulation sheet manufacturing The aerogel composition was applied as a slurry onto a 0.1 mm thick mica sheet (Famica, Muscovite), and then a 0.1 mm thick mica sheet was sandwich-type laminated and coated by rolling. The aerogel layer was then formed by drying at 60°C for 24 hours to produce a battery insulation sheet. The total thickness of the battery insulation sheet was confirmed to be 1.38 mm.

[0131] Comparative Example 2 The manufacturing method was the same as that of Example 1, except that silica fiber was used alone as the reinforcing material.

[0132] Comparative Example 3 The manufacturing method was the same as that of Example 1, except that glass wool was used alone as the reinforcing material.

[0133] Comparative Example 4 The manufacturing method was the same as that of Example 1, except that glass chopped strands were used alone as the reinforcing material.

[0134] Comparative Example 5 The manufacturing method was the same as that of Example 1, except that glass felt was used alone as the reinforcing material.

[0135] (Experimental Example) Experimental example 1: SEM analysis The cross sections of the aerogel layers of the battery insulation sheets of Examples 1, 4, and 7 and Comparative Example 1 were observed using a Hitachi S-4800 SEM, and the results are shown in Figures 3 to 6. Specifically, Figure 3 is an SEM image of Example 1, Figure 4 is an SEM image of Example 4, Figure 5 is an SEM image of Example 7, and Figure 6 is an SEM image of Comparative Example 1.

[0136] Specifically, in Comparative Example 1, no reinforcing material was present, whereas in Examples 1, 4 and 7, carbon fiber and glass wool were used in combination, and it was confirmed that the horizontal and vertical orientation of the reinforcing material was uniformly observed.

[0137] Experimental example 2: Compression characteristic evaluation The heat insulating sheets produced in the above Examples 1 to 9 and Comparative Examples 1 to 5 were used to evaluate compression characteristics.

[0138] Specifically, using UTM equipment, we took the zero point, sandwiched each insulation sheet between 1mm thick aluminum plates, and then compressed it from 0kN to 80kN at a compression speed of 0.02mm / sec to measure the thickness change, and performed a compression test. The compression rate was calculated by the thickness reduction rate at 40kN based on the thickness at 5kN. The results are shown in Table 1 below.

[0139] Experimental example 3: Thermal insulation evaluation The heat insulating properties were evaluated using the heat insulating sheets produced in the above Examples 1 to 9 and Comparative Examples 1 to 5.

[0140] Specifically, each heat insulating sheet was placed between a pair of opposing 1 mm thick aluminum plates, then placed on a heat press, and the upper plate of the heat press was heated to 350° C., while the lower plate of the heat press was not heated and was maintained at the starting temperature of 40° C. A pressure of 20 kN was then applied to the lower plate of the heat press, and the temperature of the lower plate of the heat press after 11 minutes was measured and shown in Table 1 below.

[0141] [Table 1]

[0142] From Table 1, it can be seen that in the examples, by containing the first fibrous support and the second fibrous support at a certain ratio, the porosity and orientation were improved and excellent compression properties were exhibited.

[0143] Here, from Examples 1 to 5, the evaluation results of the compression characteristics depending on the content ratio of the first fibrous support and the second fibrous support were confirmed, and it was confirmed that better physical properties were exhibited when the first fibrous support and the second fibrous support were contained in a weight ratio of 1:1 to 1:4, particularly 1:3 to 1:4.

[0144] Furthermore, from Examples 1 and 6 to 8, the evaluation results of the compression characteristics depending on the combination of the first fibrous support and the second fibrous support were confirmed, and it was confirmed that better compression characteristics were exhibited when the first fibrous support was silica fiber and the second fibrous support was glass wool or ceramic wool.

[0145] Moreover, in Example 9, a binder and a dispersant were used in combination during the production of the aerogel composition, and it was confirmed that the compression characteristics were further improved.

[0146] On the other hand, in Comparative Example 1, which does not contain a reinforcing material, the compressibility value is relatively high, but there is a problem of structural collapse due to the absence of an internal fibrous support. In addition, in Comparative Examples 2 to 5, which are cases in which a reinforcing material containing one type of fibrous support was used, it was confirmed that the compression properties were lower than those of the Examples.

[0147] In addition, with regard to thermal insulation, it can be seen from the examples that there is no temperature difference in the lower plate by using different types of reinforcing materials in combination. This means that the combination of different types of reinforcing materials improves the compressibility, which is a mechanical property, without affecting the thermal insulation.

[0148] On the other hand, it was confirmed that when the content of the first fibrous support increases beyond a certain ratio, the content of fibrous supports having a relatively long length increases, and the thermal insulation properties may decrease somewhat due to an increase in the contact thermal conductivity between internal supports.

[0149] However, it can be confirmed that, in Example 1, although a different type of fibrous support was used, the heat insulating performance was equivalent to or superior to that of Comparative Examples 2 to 5 in which a single fibrous support was used.

[0150] In particular, in Example 6, in which silica fiber, a support for improving mechanical compressibility, was used as the first fibrous support, and ceramic wool, a support with excellent heat resistance, was used as the second fibrous support, it was confirmed that the insulation properties were significantly improved.

[0151] From this, it was confirmed that excellent physical properties are exhibited when the first fibrous support and the second fibrous support are contained in a weight ratio of 1:3 to 1:4, and when a fibrous support with excellent insulating properties is mixed.

[0152] Experimental example 4: Fire resistance evaluation Of the insulating sheets produced in Examples 1 to 9 and Comparative Examples 1 to 5 above, fire resistance was evaluated using Examples 1 and 6, which have the same content ratio of the first fibrous support and the second fibrous support, i.e., 1:3.

[0153] Specifically, the heat insulating sheet was evaluated by observing changes such as the collapse of the internal structure after 10 minutes of exposure to a gas ignition torch at an exposure temperature of 1100±10°C and within a distance of 5 cm from the flame, and the fire resistance measurement photographs are shown in Figure 7. In Figure 7, the upper photograph shows the results of Example 1, and the lower photograph shows the results of Example 6.

[0154] Specifically, Example 1 is a case where silica fiber is used as the first fibrous support and glass wool is used as the second fibrous support, and Example 6 is a case where silica fiber is used as the first fibrous support and ceramic wool is used as the second fibrous support. As can be seen in FIG. 1, Example 6, which uses ceramic wool with excellent insulating performance, has excellent fire resistance, and even after the fire resistance evaluation, it does not burn and the support layer is firmly structurally maintained, confirming that it also has excellent fire resistance.

[0155] In addition, in Example 6, by using a second fibrous support material with excellent insulating performance as one of the different reinforcing materials, the support layer remained firmly held even after the fire resistance evaluation, confirming that the material has excellent fire resistance.

[0156] Although the preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the detailed description of the invention, and the accompanying drawings, and it is to be understood that these modifications also fall within the scope of the present invention. [Explanation of symbols]

[0157] 100 Battery insulation sheet 110 First base material 120 Aerogel layer 121 First fibrous support 122 Second fibrous support 130 Second base material 200 cells

Claims

1. A reinforcing material including a first fibrous support and a second fibrous support; Aerogel and a functional material comprising a binder, a dispersant, or a combination thereof; a solvent; The aerogel composition for battery insulation sheets, wherein the first fibrous support and the second fibrous support have different constituent components.

2. a material of each of the first fibrous support and the second fibrous support is at least one selected from the group consisting of glass, silica, basalt, alumina, silicon carbide, boron, ceramic, and quartz; 2. The aerogel composition for battery insulation sheet according to claim 1, wherein each of the first fibrous support and the second fibrous support has a form of at least one selected from the group consisting of powder, fiber, wool, chop, felt, batting, and lofty batting.

3. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the first fibrous support is silica fiber, and the second fibrous support is glass wool or silica wool.

4. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the first fibrous support and the second fibrous support are included in a weight ratio of 1:5 to 5:

1.

5. 2. The aerogel composition for battery insulation sheet according to claim 1, wherein each of the first fibrous support and the second fibrous support has an average length of 50 μm to 20,000 μm and an average diameter of 0.1 μm to 30 μm.

6. The aerogel has a BET specific surface area of ​​500 m 2 / g to 1,000m 2 The aerogel composition for battery insulation sheets according to claim 1, wherein the aerogel composition for battery insulation sheets has a viscosity of 1000:1 or more.

7. The average particle size of the aerogel (D 50 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the particle size is 5 μm to 200 μm.

8. The binder comprises a water-based polymer binder, 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the aqueous polymer binder is at least one selected from the group consisting of aqueous polymers, anionic water-soluble polymers, cationic water-soluble polymers, and water-dispersible polymers.

9. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the binder is contained in an amount of 0.5% by weight to 20% by weight based on the total solid content of the aerogel composition.

10. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein the dispersant is at least one selected from the group consisting of surfactants and phosphate salts.

11. The aerogel composition for battery insulation sheets according to claim 1, wherein the dispersant is contained in an amount of 0.1% by weight to 6% by weight based on the total solid content of the aerogel composition.

12. The aerogel composition for battery insulation sheets according to claim 1 , wherein the solvent is at least one selected from the group consisting of polar solvents and non-polar solvents.

13. 2. The aerogel composition for battery insulation sheets according to claim 1, wherein a weight ratio of the solvent to a total amount of solids in the aerogel composition is 1:1 to 1:

90.

14. 2. The aerogel composition for battery insulation sheet according to claim 1, wherein the reinforcing material is contained in an amount of 5 wt % to 70 wt %, the aerogel is contained in an amount of 10 wt % to 90 wt %, and the functional material is contained in an amount of 0.5 wt % to 20 wt %, based on a total solid content of the aerogel composition.

15. mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with an aerogel to produce an aerogel mixture; mixing the aerogel mixture with a reinforcing material to produce an aerogel composition; The reinforcing material includes a first fibrous support and a second fibrous support, The method for producing an aerogel composition for a battery insulation sheet, wherein the first fibrous support and the second fibrous support have different constituent components.

16. A first substrate; A second substrate; an aerogel layer formed between the first substrate and the second substrate; The aerogel layer is formed using the aerogel composition according to any one of claims 1 to 14.

17. The battery insulating sheet according to claim 16, wherein each of the first substrate and the second substrate comprises a resin, a metal, an inorganic material other than a metal, or any composite thereof.

18. 17. The battery insulation sheet of claim 16, wherein within the aerogel layer, each of the first fibrous support and the second fibrous support has a vertical orientation, a horizontal orientation, or a combination thereof.

19. Applying the aerogel composition of any one of claims 1 to 14 onto a first substrate; and laminating a second substrate on the applied aerogel composition to produce a laminate.

20. The method for producing a battery insulation sheet according to claim 19, further comprising a step of pressing and drying after the step of producing the laminate.

Citation Information

Patent Citations

  • Aerogel composition and method of manufacturing and using the same

    JP2012525290A

  • Insulating material for battery pack and battery pack

    JP2021144879A

  • Heat transfer suppression sheet and assembled battery

    JP2022024234A

  • Method for manufacturing sheet-like heat-resistant material, and laminate

    JP2022091057A

  • Manufacturing method of silica aerogel

    JP2023055573A